The Implementation Of Eclectic Method In English Of Teaching Speaking Skill At Global Learning Center - Bahing Bahing (Bajang Institute, 2026)
Is is a research of The Implementation of Eclectic Method in Teaching Speaking at Global Learning Center. Postgraduate Program University of Palangka Raya, 2026. This study was focused on the implementation of eclectic method at one of the non-formal educations in Palangka Raya, namely Global Learning Center (GLC). The English instructors used eclectic methods to maximize the teaching and learning process in order to achieve the learning objectives and to solve the problems. The eclectic method in Global Learning Center is successful because of several indicators: (1) the number of students, (2) students’ score in GLC, and (3) English centers’ reputation. The case study employed for this study because the implementation of eclectic method is still new and there is no research about it yet in Palangka Raya. This study intended to examine how the English instructors of Global Learning Center implemented the eclectic method in teaching speaking and also to investigate the challenges of implementing it.To obtain the objective, the researcher used descriptive case study. The descriptive case study used to provide rich descriptive details of the: (i) the implementation of eclectic method for teaching speaking by English instructors in Global Learning Center, (ii) the challenges of implementing eclectic method. The data were collected through observation, interview, and documentation.The result of data analysis of the implementation of eclectic method revealed that the learning activities at Global Learning Center has been followed the eclectic method’s stages. The first stage ‘Lead-In’ in eclectic method was found in English instructors’ first stage ‘Pre-Activity’. The second stage ‘Set the Task’, third stage ‘Monitor the Task’, and fourth stage ‘Task Feedback’ were found in English instructors’ second stage ‘Main- Activity’, and the fifth stage ‘Task-Related Follow Up’ was found in the English instructors’ third or last stage ‘post-activity’. Then, there were also found several teaching methods combined together in the teaching process as the characteristics of eclectic method. Based on the observation result, some of the teaching methods were found as follows (1) Direct method, (2) Audiolingual method, (3) Community Language Teaching (CLL), and (4) Communicative Language Teaching (CLT). Following that, based on the interview data, there were four challenges when implementing the eclectic method, they were (1) managing the time effectively, (2) designing an adequate lesson plan using eclectic method, (3) classroom management in students’ gap and diversity, (4) encouraging students’ resistance to speak. To solve the challenges, there were also four solutions, they were categorized as (1) setting clear rules in class, (2) planning a structured lesson plan, (3) providing propositional and fun material, (4) giving a preparation time.